1995
DOI: 10.1046/j.1537-2995.1995.351096026370.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of human platelet antigens among blood donors in northeastern Thailand

Abstract: HPA-1a was found in 100 percent of Thais, which is the same frequency as in other Asian populations but somewhat different from that in whites (97.9%). Therefore, HPA-1a will not cause neonatal alloimmune thrombocytopenia or post-transfusion purpura in Thais. According to the frequencies of HPA-2b, HPA-3a, HPA-4a, HPA-4b, HPA-5b, and Naka antigens, they may induce neonatal alloimmune thrombocytopenia, posttransfusion purpura, and platelet refractoriness in Thais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…As a matter of fact, Brazilian Caucasians and those of African descent were clustered together, but not with the Amazonas blood donors. Furthermore, it has been observed that native Brazilian populations do not present the HPA‐1 b allele (Covas et al , ; Castro et al , ; Chiba et al , ), which is markedly similar to what has been described in Asian populations (Santoso et al , ; Kim et al , ; Urwijitaroon et al , ).…”
Section: Discussionsupporting
confidence: 65%
“…As a matter of fact, Brazilian Caucasians and those of African descent were clustered together, but not with the Amazonas blood donors. Furthermore, it has been observed that native Brazilian populations do not present the HPA‐1 b allele (Covas et al , ; Castro et al , ; Chiba et al , ), which is markedly similar to what has been described in Asian populations (Santoso et al , ; Kim et al , ; Urwijitaroon et al , ).…”
Section: Discussionsupporting
confidence: 65%
“…CD36 -mice have normal tail vein bleeding times and over many years of observation do not exhibit a bleeding diathesis. Human platelet CD36 deficiency (known as the Nak a-phenotype) is common in Asian and African populations (24)(25)(26)(27), and similar to the situation in mice, is not associated with an obvious bleeding diathesis. Recently our group, in collaboration with Podrez, Hazen, and Byzova, showed that atherogenic oxLDL binds and activates platelets in a CD36-dependent manner (28).…”
Section: Introductionmentioning
confidence: 99%
“…CD36 deficiency (or Nak a -negative blood group) has been reported in Japanese (9), Thais (10) and African-Americans (11). The prevalence of CD36 deficiency in East Asian and African populations raises the possibility that the responsible variants have been selected for by malaria.…”
Section: Introductionmentioning
confidence: 99%